Закупочная логистика предприятия розничной торговли - Malakhov A. O. (Economic science today: theory and practice, 2016)
The article describes the main aspects of purchasing activity, stages of implementation of purchasing logistics are stated.
Keywords: логистика; продукция; спрос; demand; поставщики; закупочная деятельность; logistics; purchasing activity; purchasing logistics; suppliers; products; закупочная логистика